2016
DOI: 10.1016/j.jfa.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Trace ideal criteria for embeddings and composition operators on model spaces

Abstract: Let K ϑ be a model space generated by an inner function ϑ. We study the Schatten class membership of embeddings I : K ϑ ֒→ L 2 (µ), µ a positive measure, and of composition operators Cϕ :In the case of onecomponent inner functions ϑ we show that the problem can be reduced to the study of natural extensions of I and Cϕ to the Hardy-Smirnov space E 2 (D) in some domain D ⊃ D. In particular, we obtain a characterization of Schatten membership of Cϕ in terms of Nevanlinna counting function. By example this charact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…n , η) can meet at the most at one disk D ρ (z (2) m , η) for n large. Hence where the set on the right-hand side obviously is disconnected.…”
Section: Inner Functions Not Belonging To I Cmentioning
confidence: 99%
See 1 more Smart Citation
“…n , η) can meet at the most at one disk D ρ (z (2) m , η) for n large. Hence where the set on the right-hand side obviously is disconnected.…”
Section: Inner Functions Not Belonging To I Cmentioning
confidence: 99%
“…It was shown that [for instance, [10], p. 355] arclength on {z ∈ D : |u(z)| = ε} is such a measure whenever is connected and η < ε < 1.A thorough study of the class I c was given by Aleksandrov [1] who showed the interesting result that u ∈ I c if and only if there is a constant C = C(u) such that for all a ∈ D Many operator-theoretic applications are given in [1][2][3]7]. In our paper here, we are interested in explicit examples, which are somewhat lacking in the literature.…”
mentioning
confidence: 99%
“…See [20]. The class Ic also appears naturally in several recent results in the context of operator theory in KΘ2 [5–8].…”
Section: Introduction and Main Resultsmentioning
confidence: 96%
“…Conversely, take a function b ∈ BMO(σ α ) and consider the functional Φ b densely defined on K 1 θ ∩ zH 1 by formula (4). For every σ α -atom a supported on an arc ∆ we have…”
Section: Proofs Of Theorem 2 and Theorem 2 ′mentioning
confidence: 99%